Selected Anatomical Properties of Boscia angustifolia Wood - K.O., Olaoye; F.B., Okanlawon; A.L., Fayanjuola (European Scientific Journal, ESJ, 2019)
Microscopic structure of wood is identifiable with anatomy characteristics of the wood, thus the potential utility of a wood is technically dependent upon its anatomical properties. Boscia angustifolia is a lesser used species whose anatomical properties are needed to be exploited so as to known its potential utilization and peculiarity. This research therefore studied some anatomical properties of the species. Four trees were felled, and samples of 20 x 20 x 20 mm were obtained along the sampling height and radial position of the trees. Maceration and sectioning were done on the test samples, after which microscopic structure was viewed under the microscope. Mean fibre characteristics obtained (fibre length - 1.12 ± 0.24, fibre diameter - 23.67 ± 3.05 μm, lumen width – 10.09 ± 0.76 μm, and cell wall thickness – 6.87 ± 1.65 μm) were similar to those of the commonly used hardwood species in Nigeria, and vessel diameter was 65.61 ± 8.64 μm, ray height was 294.65 ± 14.12 μm and ray width was 49.32 ± 19.23 μm. The selected anatomical properties tested for Boscia angustifolia suggest that it has medium to high density, and can be used for structural purpose.